ESRA19-0285 Transnasal sphenopalatine ganglion block as a therapy for post-dural puncture headache. (30th August 2019) - Vidal, B; Mitsunaga, J; Ishizuka, P; Munechika, M; Ito, M
Abstract : Background and aims: Post-dural puncture headache (PDPH) is fronto-occipital headache that worsens in upright position; symptoms starts 2–3 days after dural puncture. Sphenopalatine ganglion block (SPGB), using topical intranasal local anesthetic, is a promising therapy for PDPH. It blocks sympathetic, parasympathetic, and somatic sensory nerves, treating via multiple mechanisms. We present 4 cases of SPGB after PDPH. Methods: Written informed consent was obtained. Blocks were performed in dorsal decubitus, under standard monitoring. Nasal vasocontriction with topical oxymetazoline 0, 05%. Cottons applicators saturated with 10% lidocaine, lubricated with 2% lidocaine gel. Wait 20 minutes positioned (posterior pharynx). Repeat this step for 10 min. Finally, put patient in Fowler's position and evaluate pain relief. Results: Case 1: Female, 35-years-old, headache. Dural puncture to exclude subarachnoid hemorrhage. Developed PDPH and, on the third day, underwent SPGB, with complete regression of symptoms. Case 2: Female, 25-years-old, headache. Dural puncture to exclude central nervous infection. After three days of PDPH, was submitted to a SPGB, with complete regression of symptoms. Case 3: Female, 30-years-old, migraine. Dural puncture to exclude infection; PDPH 7 days after. With no regression of symptoms, she underwent SPGB with partial regression of symptoms. Case 4: Female, 33-years-old, migraine. Dural puncture was performed to exclude infection, but developed PDPH. SPGB permitted complete regression of symptoms. Conclusions: SPGB is a low risk alternative to treat PDPH. An old technique, noninvasive approach. SPGB has already been described for pain relief for other types of headache. Now appears to be an emerging therapy for patients with refractory PDPH. Noninvasive, easily performed, and low risk.